2009
DOI: 10.1093/cercor/bhp149
|View full text |Cite
|
Sign up to set email alerts
|

The Selectivity and Functional Connectivity of the Anterior Temporal Lobes

Abstract: One influential account asserts that the anterior temporal lobe (ATL) is a domain-general hub for semantic memory. Other evidence indicates it is part of a domain-specific social cognition system. Arbitrating these accounts using functional magnetic resonance imaging has previously been difficult because of magnetic susceptibility artifacts in the region. The present study used parameters optimized for imaging the ATL, and had subjects encode facts about unfamiliar people, buildings, and hammers. Using both co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
179
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(203 citation statements)
references
References 84 publications
17
179
7
Order By: Relevance
“…In some task-based fMRI and lesion studies (Damasio et al, 1996;Martin et al, 1996), the LMTG has been shown to be more sensitive to certain semantic categories such as tools, while other studies have observed effects for a wide range of semantic categories (Rudrauf et al, 2008;Simmons et al, 2010), including verbs (Willms et al, 2011), suggesting that the effect reported here is not likely to be driven only by tool items. We nevertheless analyzed tool and animal items separately in our study, and found similar LMTG effects for the two categories [for tools, peak, Ϫ63, Ϫ45, Ϫ3; 3024 mm 3 (112 voxels); r peak ϭ 0.64; r cluster ϭ 0.77; p values Ͻ0.001; for animals, peak, Ϫ60, Ϫ48, Ϫ3; 3186 mm 3 (118 voxels); r peak ϭ 0.63; r cluster ϭ 0.74; p values Ͻ0.001].…”
Section: Lmtg As a Core Semantic Regionmentioning
confidence: 50%
See 1 more Smart Citation
“…In some task-based fMRI and lesion studies (Damasio et al, 1996;Martin et al, 1996), the LMTG has been shown to be more sensitive to certain semantic categories such as tools, while other studies have observed effects for a wide range of semantic categories (Rudrauf et al, 2008;Simmons et al, 2010), including verbs (Willms et al, 2011), suggesting that the effect reported here is not likely to be driven only by tool items. We nevertheless analyzed tool and animal items separately in our study, and found similar LMTG effects for the two categories [for tools, peak, Ϫ63, Ϫ45, Ϫ3; 3024 mm 3 (112 voxels); r peak ϭ 0.64; r cluster ϭ 0.77; p values Ͻ0.001; for animals, peak, Ϫ60, Ϫ48, Ϫ3; 3186 mm 3 (118 voxels); r peak ϭ 0.63; r cluster ϭ 0.74; p values Ͻ0.001].…”
Section: Lmtg As a Core Semantic Regionmentioning
confidence: 50%
“…We nevertheless analyzed tool and animal items separately in our study, and found similar LMTG effects for the two categories [for tools, peak, Ϫ63, Ϫ45, Ϫ3; 3024 mm 3 (112 voxels); r peak ϭ 0.64; r cluster ϭ 0.77; p values Ͻ0.001; for animals, peak, Ϫ60, Ϫ48, Ϫ3; 3186 mm 3 (118 voxels); r peak ϭ 0.63; r cluster ϭ 0.74; p values Ͻ0.001]. It is possible that the tool-specific effects reported in the literature originated from an LMTG region that was close to but different from ours (Simmons et al, 2010). We did show, however, that number judgment performance did not correlate with the observed object semantic LMTG network, but with parietal regions close to the classical number regions (Footnote a), suggesting that our technique has the potential to distinguish between conceptual domains.…”
Section: Lmtg As a Core Semantic Regionmentioning
confidence: 58%
“…Due to its sensitivity to higher-level factors, such as familiarity (22), and its involvement in conceptual processing (38,39), the anterior temporal cortex is thought to encode biographical information (6). Whereas our ability to localize this region validates our mapping methodology, the fact that our stimuli were not explicitly associated with any biographical information suggests that the computations hosted by this area also involve a perceptual component.…”
Section: Discussionmentioning
confidence: 64%
“…Next, we asked whether the ATL acts as a neural switchboard, performing in concert with other brain regions to enable the retrieval of different facets of person knowledge in a flexible and context-appropriate manner (study 2). We focus on the ATL because multiple lines of evidence from neuropsychology, electrophysiology, and neuroimaging have documented the critical role of the ATL in person identification (4, 5, 11-16), person-related learning (10,(17)(18)(19)(20)(21), semantic memory (6-8), and abstract social knowledge (1,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Individuals with ATL damage due to resection or stroke have multimodal person recognition deficits (34), lose access to stored knowledge about familiar people (35,36), and have difficulties learning information about new people (4,22,37,38).…”
mentioning
confidence: 99%